Optimizing the role of cadres in controlling hypertension in Sungai Rangas Ulu Village - Mustaqimah, Mustaqimah; Ariani, Malisa; Aryzki, Saftia; Saputri, Rina; Hakim, Ali Rakhman (Community Empowerment, 2025)
Hypertension is a major health problem that requires continuous management, especially in areas with limited access to health services, such as Sungai Rangas Ulu Village. Limited public knowledge and a lack of health cadre skills in monitoring blood pressure are challenges in hypertension control. This community service activity aims to optimize the role of cadres in preventing hypertension. The training involved five cadres from toddler integrated health posts (posyandu) and five cadres from elderly integrated health posts (posyandu), with methods that included theoretical delivery on hypertension and its risk factors, as well as practical use of sphygmomanometers. The training results showed that 89% of cadres experienced a significant increase in knowledge and skills. Overall, this program successfully increased cadre capacity in blood pressure monitoring and health education, which is expected to contribute to more effective hypertension control in Sungai Rangas Ulu Village. Continued mentoring is needed to ensure program sustainability and long-term positive impact.